Awareness and willingness towards pre-exposure prophylaxis against HIV infection among individuals seeking voluntary counselling and testing for HIV in Taiwan: a cross-sectional questionnaire survey. Issue 10 (16th October 2017) - Lee, Yi-Chieh; Chang, Sui-Yuan; Lin, Kuan-Yin; Chang, Lan-Hsin; Liu, Wen-Chun; Wu, Cheng-Hsin; Sun, Hsin-Yun; Hung, Chien-Ching; Chang, Shan-Chwen
Abstract : Objectives: We aimed to investigate the awareness and willingness towards pre-exposure prophylaxis (PrEP) among individuals seeking voluntary counselling and testing (VCT) for HIV in Taiwan, where PrEP is currently not reimbursed by the insurance. Methods: Between April and October 2016, a questionnaire interview was conducted among VCT clients to inquire about the attitudes towards PrEP against HIV infection. Multivariate logistic regression analysis was performed to identify the associated factors with willingness to initiate PrEP. Results: During the 6-month period, 1173 VCT clients (99.8%) completed the interviews, with 67.4% being homosexual or bisexual male. While 67.2% of the clients knew of postexposure prophylaxis, 40.2% heard of PrEP. Overall, 546 clients (46.5%) were willing to initiate PrEP and 89.5% of them would choose event-driven PrEP. In multivariate analysis, male gender (OR 1.796; 95% CI 1.165 to 2.768), full-time job (OR 1.354; 95% CI 1.052 to 1.742), one-night stand (OR 1.374; 95% CI 1.043 to 1.810), having casual sex partners within 3 months (OR 1.329; 95% CI 1.031 to 1.714), condomless anal sex (OR 1.405; 95% CI 1.122 to 1.878) and ever having chemsex or attending a drug party in the past 1 year (OR 2.571; 95% CI 1.541 to 4.287), regular screening for HIV infection (OR 1.321; 95% CI 1.021 to 1.711) and knowledge of PrEP (OR 1.504; 95% CI, 1.159 to 1.953) were associated with willingness to initiate PrEP. Conclusions: Understanding the willingness to initiate PrEP against HIV among the VCT clients in Taiwan, which was associated with male gender, risky sexual behaviours and awareness of PrEP, will help inform the implementation of PrEP programme.